Pendekatan Humanisme Dalam Proses Pembelajaran Mata Ajar Pendidikan Agama Islam - Azizah, Nur; Sobandi, Ade; Fatadona, Hendra (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2025)
Modern education increasingly requires an approach that prioritizes the holistic development of individuals. Education systems focused on outcomes have often been criticized for neglecting human aspects, such as mental well-being and self-development. Humanism emerges as a response to the need to honor students' dignity, potential, and freedom in their learning. The study aims to examine the application of humanistic principles in the teaching and learning process of Islamic Religious Education at Aisyiyah Boarding School Bandung. Primary data were obtained through interviews and observations with several teachers and students, while secondary data were gathered from the school's website content. The findings indicate that this humanistic approach enables students to: appreciate individuality and the potential of learners, develop emotional intelligence, create a positive learning environment, encourage meaningful learning, foster a critical and creative attitude and support holistic development. Keywords: Humanistic Approach; Education; Freedom to Learn; Humanizing Humans